PERSEPSI NASABAH TERHADAP PRODUK TABUNGAN IB HASANAH DAN DAMPAKNYA TERHADAP MINAT MENABUNG NASABAH - Wajo, Abd Rauf; Betawi, Erna (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
This study aims to determine customer perceptions of iB Hasanah savings and the impact on decisions to become customers at Bank Syariah Indonesia (BSI) Ternate Hasan Esa Ternate. This research using qualitative research to explain the facts objectively according to the data obtained through observation data sources, interviews and documentation at the research location for further analysis using a qualitative descriptive approach. The results of the study indicate that customer perceptions of the iB Hasanah savings product are: first, customers know that this product is part of the implementation of religious values in saving assets or money in Islamic banking. Second, customers have confidence that their savings must be managed by trustworthy people so that their security and blessings are guaranteed. Third, customers choose the iB Hasanah savings product which is managed with the principle of profit sharing. Several customer perceptions of the iB Hasanah savings product have an impact on customer interest in saving with the iB Hasanah savings product. This interest arose from customers' perceptions of their knowledge of iB Hasanah products, their trust in Islamic banks and iB Hasanah savings products, as well as managing savings funds in iB Hasanah products with the principle of profit sharing.